SOSIALISASI DETEKSI DINI PENYAKIT JANTUNG BAWAAN PADA ANAK DI RSUD KABUPATEN KEDIRI - Rahman, Mahrus Abdur; Hidayat, Taufiq; Utamayasa, I Ketut Alit; Wicaksono, Henry; Nastiti, Prima Hari (Universitas Mataram, 2024)
Congenital Heart Disease (CHD) occurs in 6 to 8 out of every 1,000 live births. CHD is one of the most common congenital anomalies, with a mortality rate of up to 25% in the first year of life. CHD is a structural and functional abnormalities that develop during embryogenesis. Delayed diagnosis of CHD leads to increased morbidity and mortality. A community service activity was conducted in Kediri, East Java, to raise awareness among medical personnel about early detection of CHD, followed by examinations using pulse oximetry and echocardiography. The education method included seminars and training sessions covering early detection, diagnosis, and management of CHD. The examinations were performed by pediatric cardiology consultants. Pre-test and post-test evaluations were conducted to assess the knowledge level of medical personnel. The activity involved 100 participants, including specialists, general practitioners, midwives, and nurses. The average pre-test score was 58.57/100, with 7 participants achieving a perfect score. By the end of the training, the average post-test score increased to 72.06/100, with 25 participants obtaining perfect scores. A total of 27 children underwent echocardiography; 20 were diagnosed with acyanotic CHD, 2 with cyanotic CHD, and 5 were normal. In the pulse oximetry examinations, all infants had oxygen saturation levels of 95% or higher, with no difference greater than 3% between pre- and post-ductal locations. The conclusion is that education through seminars and training can improve medical personnel's knowledge of early detection of CHD in children.